Expression, Oppression and Queer Bodies: A pilot study exploring the lived experiences of LGBTQ+ medical students in the UK. - Bintley, Helen (Advanced Journal of Professional Practice, 2023)
This article details a qualitative study exploring the lived experiences of LGBTQ+ medical students in one university in the UK. Few studies exist, especially those that ARTICLES AJPP Vol 4, No1 (2023) 2 directly include LGBTQ+ voices, that explore the lived experiences of LGBTQ+ medical students. Those that exist suggest that there are significant, ongoing problems with heteronormativity in medical schools and society and more could be done to appropriately support this student population during their medical studies. Therefore, in this study the author set about exploring the lived experiences of LGBTQ+ medical students using first-person narratives to capture their lives in their own words. The author used an adapted qualitative methodology and method underpinned by philosophical concepts including post[1]structuralism and materialism to realise their study aims. Outcomes showed that fear and violence but also subversion of heteronorms, community formation and protection, and ‘queer joy’ were a significant part of the students’ lived experiences. Interpretive understandings also illustrated perceptions of ‘queer bodies’ as other and/or normative and intersectional repression and oppression as an ongoing, significant experience for participants. Here the author understands queer bodies to be constantly redefined understandings of queer identity emerging from entangled relationships between gender and sexuality ‘norms’. In line with intersectionality and decolonisation literature the author argued that medical curriculum is an act of LGBTQ+ related, epistemic violence and highlighted the importance of intersectionality and intersectional transdisciplinarity in enacting change in this respect. Finally, it is argued, in line with participants’ documented experiences that queerness and ‘’queer bodies’ are both personal and community experiences/entities and awareness of this relationship is important for re-considering LGBTQ+ related stigma and healthcare inequality.